Pregravidal preparation for women with hyperhomocysteinemia - L A Ozolinya; A Z Kashezheva (IP Berlin A.V., 2013)
The paper presents the results of a study of pregravidal training efficacy in women with hyperhomocysteinemia (HHC). 136 patients, among them: 30 women with mutations GGC against methylenetetrahydrofolate, 71 patients with GHz without this mutation and 35 women with normal levels of homocysteine (HC) in the blood plasma were constantly monitored. Risk factors for HHC were: anemia, hormonal contraception, diseases of the gastrointestinal tract, the lack of food folate, high coffee consumption (more than 2 cups per day), smoking. To reduce HC following treatment was appointed: folic acid (3 mg/day) and Vitrum Prenatal Forte multivitamin complex (1 tab/day). A significant decrease in the homocysteine concentration in blood plasma was noted on the first month of treatment, however, the level of GC in women who have not had methylenetetrahydrofolate mutation than in patients with this mutation was more reducing more quickly. Thanks to the adequate pregravidal preparation the majority of patients were able to normalize the level of homocysteine in blood and reduce the risk of obstetric complications in the event of pregnancy.